Study of glycerol electrochemical conversion into added-value compounds / Lee Ching Shya - Lee, Ching Shya (2016)
The price of crude glycerol has significantly decreased worldwide because of its oversupply. Many chemical and biological processes have been proposed to transform glycerol into numerous added-value products, such as glycolic acid, 1,3-propanediol (1,3-PDO), 1,2-propanediol (1,2-PDO), glyceric acid, and lactic acid. However, these processes suffer several drawbacks, including high production cost. Therefore, in this study, a simple and robust electrochemical synthesis was developed to convert glycerol into various added-value compounds. This study reports for the first time the use of Amberlyst-15 as a reaction medium and redox catalyst for electrochemical conversion of glycerol. In the first part, the electrochemical performance of Amberlyst-15 over platinum (Pt) electrode was compared with that of conventional acidic (H2SO4) and alkaline (NaOH) media. Other parameters such as reaction temperature [room temperature (27 °C) to 80 °C] and applied current (1.0 A to 3.0 A) were also examined. Under the optimized experimental condition, this novel electrocatalytic method successfully converted glycerol into glycolic acid after 8 h of electrolysis, with a yield of 45% and selectivity of 65%, as well as to glyceric acid after 3 h of electrolysis, with a yield of 27% and selectivity of 38%. In the second part of this study, two types of cathode electrodes, namely, activated carbon composite (ACC) and carbon black diamond (CBD) electrodes, were used in electrochemical conversion of glycerol. To the best of our knowledge, electrochemical studies of glycerol conversion using these electrodes have not been reported yet. Glycerol was also successfully reduced to lactic acid, 1,2-PDO, and 1,3-PDO, in addition to oxidation compounds (e.g. glycolic acid). Three operating parameters, namely, catalyst amount (6.4% to 12.8% w/v), reaction temperature [room temperature (27 °C) to 80 °C], and applied current (1.0 A to 3.0 A), were tested. In the presence of 9.6% w/v Amberlyst-15 at 2.0 A and 80 °C, the selectivity of glycolic acid can reach 72% and 68% (with yield of 66% and 58%) for ACC and CBD electrodes, respectively. Lactic acid was obtained as the second largest compound, with selectivity of 16% and yield of 15% for the ACC electrode and 27% selectivity and 21% yield for the CBD electrode. Finally, electro-oxidation and electroreduction of glycerol were performed in a two-compartment cell separated by a cation exchange membrane (Nafion 117). This study only focused on the electroreduction region. Three cathode electrodes (Pt, ACC, and CBD) were evaluated under the following conditions: 2.0 A, 80 °C, and 9.6% w/v Amberlyst-15. ACC demonstrated excellent performance in the electroreduction study and successfully reduced glycerol to 1,2-PDO, with a high selectivity of 85%. The selectivity of 1,2-PDO on Pt and CBD was 61% and 68%, respectively. Acetol and diethylene glycol were also obtained. The reaction mechanisms underlying the formation of these products are then proposed.